Muscarinic acetylcholine receptors activate expression of the EGr gene family of transcription factors - Wegner, Michael; et al. (Journal of Biological Chemistry, 1998)
In order to search for genes that are activated by muscarinic acetylcholine receptors (mAChRs), we used an mRNA differential display approach in HEK293 cells expressing m1AChR. The zinc-finger transcription factor genes Egr-1, Egr-2, and Egr-3 were identified. Northern blot analyses confirmed that mRNA levels of Egr-1, Egr-2, and Egr-3 increased readily after mAChR stimulation and that a maximum was attained within 50 min. At that time, Egr-4 mRNA was also detectable. Western blots and electromobility shift assays demonstrated synthesis of EGR-1 and EGR-3, as well as binding to DNA recognition sites in response to m1AChR activation. Activation of m1AChR increased transcription from EGR-dependent promoters, including the acetylcholinesterase gene promoter. Activity-dependent regulation of Egr-1 mRNA expression and EGR-1 protein synthesis was also observed in cells expressing m2, m3, or m4AChR subtypes. Increased EGR-1 synthesis was mimicked by phorbol myristate acetate, but not by forskolin, and receptor-stimulated EGR-1 synthesis was partially inhibited by phorbol myristate acetate down- regulation. Together, our results demonstrate that muscarinic receptor signaling activates the EGR transcription factor family and that PKC may be involved in intracellular signaling. The data suggest that transcription of EGR-dependent target genes, including the AChE gene, can be under the control of extracellular and intracellular signals coupled to muscarinic receptors.
UnivIS-Import:2015-03-05:Pub.1998.med.IB.LPCIPDBI.muscar_10